Tidal Analysis of Long Series - Franco, A. S.; Harari, J. (The International Hydrographic Review, 2015)
It is shown how M (≥5) sets of Fourier coefficients obtained from M successive Fast Fourier Transforms (FFT) of 214 tapered hourly heights can be combined to obtain the harmonic constants of the clusters of the main astronomical and shallow-water constituents and their respective satellites. It is also shown how the clusters of the shallow-water constituents are formed.